Diets Low in Saturated Fat with Different Unsaturated Fatty Acid Profiles Similarly Increase Serum-Mediated Cholesterol Efflux from THP-1 Macrophages in a Population with or at Risk for Metabolic Syndrome: The Canola Oil Multicenter Intervention Trial. Issue 5 (2nd May 2018) - Liu, Xiaoran; Garban, Josephine; Jones, Peter J; Vanden Heuvel, Jack; Lamarche, Benoît; Jenkins, David J; Connelly, Philip W; Couture, Patrick; Pu, Shuaihua; Fleming, Jennifer A; West, Sheila G; Kris-Etherton, Penny M
Abstract: Background: Cholesterol efflux plays an important role in preventing atherosclerosis progression. Vegetable oils with varying unsaturated fatty acid profiles favorably affect multiple cardiovascular disease risk factors; however, their effects on cholesterol efflux remain unclear. Objective: The objectives of this study were to examine the effects of diets low in saturated fatty acids (SFAs) with varying unsaturated fatty acid profiles on serum-mediated cholesterol efflux and its association with the plasma lipophilic index and central obesity. Methods: The present study is a randomized, crossover, controlled-feeding study. Participants [men: n  = 50; women: n  = 51; mean ± SE age: 49.5 ± 1.2 y; body mass index (in kg/m 2 ): 29.4 ± 0.4] at risk for or with metabolic syndrome (MetS) were randomly assigned to 5 isocaloric diets containing the treatment oils: canola oil, high oleic acid–canola oil, DHA-enriched high oleic acid–canola oil, corn oil and safflower oil blend, and flax oil and safflower oil blend. These treatment oils were incorporated into smoothies that participants consumed 2 times/d. For a 3000-kcal diet, 60 g of treatment oil was required to provide 18% of total energy per day. Each diet period was 4 wk followed by a 2- to 4-wk washout period. We quantified cholesterol efflux capacity with a validated ex vivo high-throughput cholesterol efflux assay. Statistical analyses were performed with the use of the SAS mixed-model procedure. Results: The 5 diets increased serum-mediated cholesterol efflux capacity from THP-1 macrophages similarly by 39%, 34%, 55%, 49% and 51%, respectively, compared with baseline ( P  < 0.05 for all). Waist circumference and abdominal adiposity were negatively correlated with serum-mediated cholesterol efflux capacity ( r  = −0.25, P  = 0.01, r  = −0.33, P  = 0.02, respectively). Conclusion: Diets low in SFAs with different monounsaturated fatty acid and polyunsaturated fatty acid profiles improved serum-mediated cholesterol efflux capacity in individuals with or at risk for MetS. This mechanism may account, in part, for the cardiovascular disease benefits of diets low in SFAs and high in unsaturated fatty acids. Importantly, central obesity is inversely associated with cholesterol efflux capacity. This trial was registered at www.clinicaltrials.gov as NCT01351012.